2016
DOI: 10.1177/1071100716669359
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Stability of Posterior Antiglide Plating in Osteoporotic Pronation Abduction Ankle Fracture Model With Posterior Tibial Fragment

Abstract: The clinical implication of this biomechanical study is that the posterior antiglide plating might be advantageous in patients with osteoporotic pronation abduction stage III ankle fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Serveral studies have demonstrated that the posterolateral approach allows for a better quality of reduction of the PM fragment, particularly in the presence of smaller, depressed and intercalary fragments [5,19,[36][37][38][39][40]. Biomechanically, posterior screws and antiglide plates to the PM and distal fibula provide more stability than anterior-to posterior screws or lateral plates, respectively [33,36,37,41].…”
Section: Surgeon-related Risk Factorsmentioning
confidence: 99%
“…Serveral studies have demonstrated that the posterolateral approach allows for a better quality of reduction of the PM fragment, particularly in the presence of smaller, depressed and intercalary fragments [5,19,[36][37][38][39][40]. Biomechanically, posterior screws and antiglide plates to the PM and distal fibula provide more stability than anterior-to posterior screws or lateral plates, respectively [33,36,37,41].…”
Section: Surgeon-related Risk Factorsmentioning
confidence: 99%
“…In osteoporotic bone, a locking plate fixation might be advantageous. 126 Important structures that are at risk are the sural nerve, peroneal tendons and the flexor hallucis longus muscle. 121 , 127 In a cadaveric study, lesions to the tibialis anterior tendon were seen through posterior to anterior K-wires.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…7,41 A buttress plate or lag screw can be used to fix the fracture. 42 This is biomechanically stronger, and a more logical approach than a screw sited from the anterior tibia, which commonly pushes the fragment away from, rather than lagging it to, the tibia. 43 The same incision can be used for Weber B/SER type fractures to fix the fibular fracture with an anti-glide plate.…”
Section: Cite This Articlementioning
confidence: 99%